2019
DOI: 10.1038/s41598-019-50584-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impacts of Drought on Grassland Net Primary Production at the Global Scale

Abstract: Quantitatively assessing the impacts of drought on grassland has significant implications to understand the degradation mechanism and prevention degraded grassland. In this study, we analyzed the relationship between grassland drought and grassland Net Primary Productivity (NPP) based on the self-calibrated Palmer Drought Severity Index (scPDSI) from 1982 to 2008. The results showed that the global grassland scPDSI value had a slightly increasing trend with the rate of 0.0119 per year (R2 = 0.195), indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 47 publications
5
16
0
Order By: Relevance
“…Satellite-based observation offers a method for monitoring and characterizing the spatiotemporal dynamics of vegetation under changing climates [12], which is especially valuable for remote areas such as most Australia's interior with very sparse monitoring sites. Traditional reflectance-based vegetation indices are widely applied to assess the effects of extreme drought on ecosystem functioning and vegetation productivity at a regional, continental, or global scale [8,[13][14][15][16][17]. Dramatic impacts of climate extremes on vegetation dynamics (as measured by EVI) with abrupt changes in phenology and productivity over southeast Australia demonstrates that semiarid ecosystems exhibit the largest sensitivity to hydro-climatic variations [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Satellite-based observation offers a method for monitoring and characterizing the spatiotemporal dynamics of vegetation under changing climates [12], which is especially valuable for remote areas such as most Australia's interior with very sparse monitoring sites. Traditional reflectance-based vegetation indices are widely applied to assess the effects of extreme drought on ecosystem functioning and vegetation productivity at a regional, continental, or global scale [8,[13][14][15][16][17]. Dramatic impacts of climate extremes on vegetation dynamics (as measured by EVI) with abrupt changes in phenology and productivity over southeast Australia demonstrates that semiarid ecosystems exhibit the largest sensitivity to hydro-climatic variations [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2017), in their field manipulation experiment in the semiarid C 3 steppe of Inner Mongolia, China, showed similar magnitudes of reduction in GPP and ecosystem respiration in response to warming. Although a meta‐analysis demonstrated that ecosystem respiration was more sensitive to warming than GPP in temperate grasslands, differences in photosynthetic pathway and phenology likely contribute to variable responses (Q. Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although a meta-analysis demonstrated that ecosystem respiration was more sensitive to warming than GPP in temperate grasslands, differences in photosynthetic pathway and phenology likely contribute to variable responses (Q. Wang et al, 2019).…”
Section: Does Warming Alter C Allocation In Perennial Grass?mentioning
confidence: 99%
“…The data are widely used in monitoring global and regional ecosystem carbon cycles (Cai et al 2020;Guo et al 2019;Liu et al 2015;Liu et al 2019) (Palmer 1965), and self-calibrated Palmer Drought Severity Index (scPDSI) (Wells et al 2004). PDSI was calculated based on temperature and precipitation information and widely applied for agricultural drought monitoring since 1965 (Liu et al 2016;Wang et al 2019;Wu et al 2020). The scPDSI was calculated with monthly precipitation and air temperature-driven observations available from the Climatic Research Unit (CRU) high-resolution surface climate data set CRU TS4.03 (Schrier et al 2013;Wells et al 2004).…”
Section: Gpp Et and Scpdsi Datamentioning
confidence: 99%